Peningkatan Menulis Huruf Jawi melalui Think Talk Write pada Siswa Kelas 7/2 Sampan Vittaya Thailand - Sulaiha Samoh; Etin Pujihastuti; Bivit Anggoro Prasetyo Nugroho (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to improve students’ ability to write Jawi script through the implementation of the Think Talk Write (TTW) cooperative learning model in class 7/2 at Sampan Vittaya School, Thailand. The research was conducted using Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through writing tests, observations, and documentation. The results of the first cycle showed that students began to understand the basic forms of Jawi letters, although errors in letter connection, direction, and neatness were still evident. The improvement became more significant in the second cycle, where students demonstrated better accuracy in letter formation, consistency in connections, and overall neatness of writing. The TTW model encouraged students to think independently, participate actively in group discussions, and strengthen understanding through structured writing activities. The increase in average scores and the rise of mastery learning from 57% to 86% indicated the effectiveness of the TTW model in enhancing students' Jawi writing skills. These findings suggest that TTW can serve as an alternative approach for Jawi script instruction in schools with similar cultural and linguistic backgrounds. The study also opens opportunities for future research involving digital learning media or comparative studies with other cooperative learning models.